2011
DOI: 10.5142/jgr.2011.35.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Management of Radiation Injuries by Panax ginseng Extract

Abstract: Chemical radiation protection is an important strategy to protect living beings against the deleterious effects of radiation. In the present study, the radioprotective effect of hydro-alcoholic extract of Panax ginseng extract (PGR-HAE) was studied on radiation-induced deleterious alterations in Swiss albino mice. Oral administration of such extract (25 mg/kg b wt/day/animal) for 5 consecutive days, half an h. before whole-body exposure to 6 Gy gamma radiation, enhanced the 30 days survival and also inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The lung tissue levels of GSH, a free radical scavenger and cosubstrate for GPx, were lower at 10 days after irradiation, which may have been caused by the increased consumption of this compound to combat the elevated oxidative stress at the time. The reduction in oxidative stress by the PGE pretreatments prevented this decrease in GSH level, which was similar to the results reported by previous studies (Verma et al ., ; Ramesh et al ., ). At 2 and 10 days after irradiation, the results for the GSH contents in the PGE pretreatment groups were related to those for the MDA levels in these groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The lung tissue levels of GSH, a free radical scavenger and cosubstrate for GPx, were lower at 10 days after irradiation, which may have been caused by the increased consumption of this compound to combat the elevated oxidative stress at the time. The reduction in oxidative stress by the PGE pretreatments prevented this decrease in GSH level, which was similar to the results reported by previous studies (Verma et al ., ; Ramesh et al ., ). At 2 and 10 days after irradiation, the results for the GSH contents in the PGE pretreatment groups were related to those for the MDA levels in these groups.…”
Section: Discussionmentioning
confidence: 97%
“…The oxidative damage induced by ·OH can be efficiently reduced by the direct scavenging of ·OH produced by the radiolysis of water and by preventing the formation of ·OH via the Fenton reaction. In addition to the effective ·OH scavenging and ferrous metal‐ion‐chelating activities of whole ginseng extract or isolated ginsenosides, which were previously verified through in vitro experiments, several authors have reported that ginseng increases the activity of endogenous antioxidant enzymes, such as SOD, catalase, and GSH peroxidase (GPx), under basal oxidative stress conditions, and it prevents the reduction in their activity caused by elevated oxidative stress (Chang et al ., ; Verma et al ., ; Ramesh et al ., ). At the early stage of RILI, the influx of inflammatory cells such as macrophages to an injury site is induced by the altered expression of proinflammatory cytokines, and the influx may induce additional ROS production by these cells and chronic oxidative stress (Sisto et al ., ; Fleckenstein et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines may be necessary for recovery of the hematopoietic system and induction of the immune system to protect against radiation exposure. Furthermore, oral administration of ginseng root extracts to albino mice prior to whole-body exposure to γ-radiation increased survival rates and life expectancy, restored the levels of a number of endogenous antioxidants, including GST, CAT and SOD-1, and inhibited radiation-induced sickness and weight loss (92). These extracts also significantly decreased the increased level of radiation-mediated lipid peroxidation (92,96).…”
Section: Zingiber Officinalementioning
confidence: 89%
“…Ginseng contains various types of ginsenosides (major active components), kaempferol, caffeic acids, acidic polysaccharides and palmitic acids in its stem, leaves and roots. The majority of the evidence for the radioprotective properties of ginseng has been accumulated over the last several decades (90)(91)(92)(93). For example, the administration of ginseng extracts resulted in suppression of radiation-induced inflammatory response through inhibition of cyclooxygenase-2 overexpression, as well as recovery of spleen and thymus damage induced by radiation exposure in mouse models (94).…”
Section: Zingiber Officinalementioning
confidence: 99%
“…P. ginseng has been commonly used to treat a wide variety of diseases [43]. Previous studies reported that P. ginseng beneficially affected side effects or adverse effects during the IRs [44], [45]; however, no study has been conducted regarding RILI.…”
Section: Discussionmentioning
confidence: 99%